Studi Keanekeragaman Mikroalga di Perairan Sungai Barumun - Ria Resti Fauzi Pane; Arman Harahap (BIOEDUSAINS:Jurnal Pendidikan Biologi dan Sains, 2023)
This study aims to determine the diversity of microalgae in the waters of the Barumun River as basic data. This study conducted a survey on the diversity of microalgae in the waters of the Barumun River which is located in Panai Hulu Regency, Labuhanbatu Regency, North Sumatra Province from October to December 2022. The method used is exploration. Determination of the sampling was carried out by systematic purposive sampling. Sampling was carried out through three points, namely the upstream, middle and downstream of the Barumun River. This study found 47 species of microalgae belonging to 42 genera and 27 orders, members of Chlorophyta and Bacillariophyceae as the most abundant microalgae. At point 1 found 36 species, while at point 2 found 30 species, and at point 3 as many as 22 species. The physicochemical factors of the Barumun River waters were also measured, the average water temperature was 27 RAM C, the average pH was 6.7, and the average water brightness was 57 cm. This study concluded that environmental factors greatly affect the diversity of microalgae in the Barumun River waters. Keywords: Diversity, Microalgae, Barumun River